2017
DOI: 10.18632/aging.101185
|View full text |Cite
|
Sign up to set email alerts
|

Genomic deletion of GIT2 induces a premature age-related thymic dysfunction and systemic immune system disruption

Abstract: Recent research has proposed that GIT2 (G protein-coupled receptor kinase interacting protein 2) acts as an integrator of the aging process through regulation of ‘neurometabolic’ integrity. One of the commonly accepted hallmarks of the aging process is thymic involution. At a relatively young age, 12 months old, GIT2−/− mice present a prematurely distorted thymic structure and dysfunction compared to age-matched 12 month-old wild-type control (C57BL/6) mice. Disruption of thymic structure in GIT2−/− (GIT2KO) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 141 publications
(180 reference statements)
1
23
0
Order By: Relevance
“…These effects allow one for introducing a capacitive susceptibility that can be resonates with self-induction effect of helical coils in G proteins. Table 5 indicates the calculated helical proteins self-induction (of some G-proteins component) [63][64][65][66][67][68][69][70][71][72][73][74] through resonance with capacitances of several phospholipids membranes. Due to the greater inductance compared to conductance in coils, the helical coils of DNA, mRNA, and trance membrane proteins can be resonate with a capacitive susceptibility of phospholipids capacitors in biological phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…These effects allow one for introducing a capacitive susceptibility that can be resonates with self-induction effect of helical coils in G proteins. Table 5 indicates the calculated helical proteins self-induction (of some G-proteins component) [63][64][65][66][67][68][69][70][71][72][73][74] through resonance with capacitances of several phospholipids membranes. Due to the greater inductance compared to conductance in coils, the helical coils of DNA, mRNA, and trance membrane proteins can be resonate with a capacitive susceptibility of phospholipids capacitors in biological phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Additional investigations revealed that GIT2 interacts with many proteins involved in multiple signaling pathways linked to aging such as ATM, p53 and BRCA1. All of these proteins are involved in stress-responsive cascades and play important roles in cell cycle/DDR control, circadian clock regulation [ 157 , 210 , 211 ] and generation of SASP phenotypes in immune tissues [ 211 ]. Ectopic elevation of GIT2 expression in neuronal and non-neuronal tissues is able to attenuate the extent of DNA DSB damage induced by both ionizing radiation and chemotherapeutic DNA-damaging agents (cisplatin) [ 210 ].…”
Section: G Protein-coupled Receptor Systems: Intersections With Dnmentioning
confidence: 99%
“…Further reinforcing this permissive role of GIT2 in the aging process, it was shown that genomic deletion of GIT2 resulted in an accelerated rate of γ-H 2 AX lesion inclusion in central nervous cortex tissue in experimental mice [ 210 ]. In addition to the damage caused to brain tissues in GIT2 knockout (GIT2KO) mice, it was recently demonstrated that genomic deletion of GIT2 led to a significant co-reduction of multiple circadian clock-related mRNA transcripts in a broad range of immunological tissues including spleen, thymus and multiple lymph nodes [ 211 ]. This downregulation of GIT2 with associated clock-related proteins has been associated with premature aging (evidenced by accelerated thymic involution), the creation of a SASP-like phenotype and DDR functions [ 211 ].…”
Section: G Protein-coupled Receptor Systems: Intersections With Dnmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] As the cradle and educators of immature T-cells, thymus serves as dynamic role to mediate lymphopoietic activity. [8,9] Thymus recession also impairs the capacity to recover adaptive immunity following immune depletion in patients. Early thymus shares the same rudiment with parathyroid for development, [4] with original roles in enhancing reproductive system and adolescence growth, which gives obvious evidence as an erstwhile endocrine organ.…”
Section: Introductionmentioning
confidence: 99%